Effects of aerobic and resistance exercise intensities on 24-hours blood pressure in normotensive women - Aparecido Pimentel Ferreira; Bruno Rafael Martins Campos; Édis Rodrigues Junior; Guilherme Morais Puga; Ciro José Brito (Universidade Estadual Paulista (UNESP), 2013)
The present study aimed to determine the effect of the intensity of aerobic and resistance exercise on the 24h BP response in normotensive women. Twenty-four women (aged 33 ± 9 years) performed five experimental sessions in randomized order: CON - no exercise; AE50 - 50% of heart rate reserve (HRR); AE70 - 70% of HRR; RE40 - 40% of 1repetition maximum (RM) and RE70 - 70% of 1RM. Systolic and diastolic BP and HR measurements were measured during 24h post-exercise at the participant's workplace. The AE50, AE70 and RE40 sessions led to the greatest and longest-lasting effects on the SBP, which persisted for up to 24h. For the DBP, the experimental sessions led to similar results; post exercise hypotension was observed until 7h post-exercise, with the exception of the AE70 session, which produced effects that persisted for 24h. Results shows that both aerobic and resistance exercise performed during the morning can decrease the mean BP above the baseline lasting 24 hours during a normal daily work. The aerobic exercise performed around 50% of HRR can better regulate both systolic and diastolic BP in this population.